Refractory composite sheet
By using composite sheet design with textile components and polymer coatings on cargo container walls, the problem of difficult to provide efficient fire protection and weight reduction in the prior art is solved, and better flame barrier properties and fire resistance are achieved.
Patent Information
- Application Number
- CN202380056738.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-09
- Filing Date
- 2023-06-07
- Publication Date
- 2025-04-01
AI Technical Summary
The prior art is difficult to provide refractory composite sheets for cargo container walls, especially on container curtain walls used in aircraft, which not only improves fire protection but also reduces weight.
The composite sheet design is employed including textile parts and polymer coatings, where the textile parts are blended with woven fabrics and nonwoven fabrics of continuous filament yarns and bonded or stitched between fabric structures to enhance bond strength, and the coating provides additional UV and chemical resistance.
It achieves better flame barrier properties and fire resistance, while reducing weight, and is suitable for curtain wall materials for aircraft cargo containers.
Smart Images

Figure CN119744222A_ABST
Abstract
Description
Background of the Invention 1. Technical Field
[0002] The disclosed embodiments generally relate to a composite sheet material having fire resistant properties. The sheet material can be used as curtain wall for fire resistant cargo containers, particularly containers used in aircraft. 2. Background technology
[0003] The amount of cargo carried in both passenger and cargo aircraft has been increasing for many years. At the same time, there is a growing concern about the risk of fire in cargo containers due to the increase in the amount of power sources in the cargo, such as high-density energy storage devices or other battery types. Five recent developments in fire-resistant composite sheets for cargo container walls are described below.
[0004] U.S. Patent No. 9,296,555 to Kawka and Chang relates to a non-rigid composite sheet comprising, in sequence, (i) a first component having an areal density of 88 to 678 gsm, the first component comprising a first filament yarn fabric having a tenacity of at least 11 grams per decitex (g / dtex) and a first polymer layer that is UV-impermeable and weatherproof, (ii) a second component having an areal density of 30 to 237 gsm, the second component comprising a flame retardant substrate and an inorganic fire resistant layer, and (iii) a third component having an areal density of 88 to 678 gsm, the third component comprising a second filament yarn fabric having a tenacity of at least 11 grams per decitex and a second polymer layer that is impact-resistant and scratch-resistant, the second fabric of the third component being adjacent to the fire resistant layer of the second component.
[0005] U.S. Patent No. 9,302,845 to Kawka and Chang discloses a non-rigid composite sheet comprising, in sequence, a first component having an areal density of 102 to 678 gsm, the first component comprising a first filament yarn fabric having a tenacity of at least 11 g / dtex and a first polymer layer that is UV-impermeable and weatherproof; a second component having an areal density of 10 to 170 gsm, the second component comprising a flame-retardant inorganic fire-resistant layer adjacent to at least one protective polymer layer; and a third component having an areal density of 102 to 678 gsm, the third component comprising a second filament yarn fabric having a tenacity of at least 11 g / dtex and a second polymer layer that is impact-resistant and scratch-resistant, the second fabric of the third component being adjacent to the fire-resistant layer of the second component.
[0006] U.S. Patent No. 10,457,013 to Kawka and Perez teaches a non-rigid composite sheet comprising, in sequence, (i) a first component having an area weight of 88 to 678 gsm, the first component comprising a first filament yarn fabric having a tenacity of at least 11 g / dtex and a first polymer layer that is UV-impermeable and weather-resistant, (ii) a second component having an area weight of 120 to 430 gsm, the second component comprising a flame-retardant paper, and (iii) a third component having an area weight of 88 to 678 gsm, the third component comprising a second filament yarn fabric having a tenacity of at least 11 g / dtex and a second polymer layer that is impact-resistant and scratch-resistant, the second fabric of the third component being adjacent to the paper of the second component.
[0007] U.S. Patent No. 9,993,989 issued to Kawka describes a non-rigid composite sheet comprising, in sequence, (i) a first component comprising a first continuous filament yarn fabric having a tenacity of at least 11 grams per dtex and a first polymer layer, (ii) a second component comprising at least one second continuous filament glass yarn fabric, the second fabric being adjacent to the first fabric of the first component, and (iii) a third component comprising a second polymer layer.
[0008] U.S. Patent No. 10,300,677 to Kawka relates to a non-rigid composite sheet comprising, in sequence, (i) a first component comprising at least one first continuous filament yarn fabric having a tenacity of at least 11 g / dtex and a first polymer layer, (ii) a second component comprising at least one second continuous filament glass yarn fabric, the at least one second fabric being adjacent to the at least one first fabric of the first component, and (iii) a third component comprising a second polymer layer.
[0009] However, there remains a need and desire for additional fire resistant composite sheets for cargo container walls that will provide improved fire protection. Further weight reduction is also desired. Summary of the invention
[0010] In one aspect, the present disclosure provides a composite sheet 11 comprising a textile component 12 having a first surface 13 and a second surface 14, and a first polymer coating 15 on the first surface 13 of the textile component 12. The textile component 12 further comprises
[0011] a fabric structure 16 of a woven fabric of at least one continuous filament yarn, the fabric having an area weight of about 70 to about 508 gsm, and
[0012] A nonwoven fabric structure 17 comprising a blend of discontinuous oxidized polyacrylonitrile fibers and silica fibers, wherein the oxidized polyacrylonitrile fibers are present in an amount of about 30 to about 70 weight percent of the combined weight of the oxidized polyacrylonitrile fibers and the silica fibers. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 is an exploded end view of composite sheet 11 according to an exemplary embodiment.
[0014] Figure 2 is an end view of textile component 12 illustrating stitching through textile structures 16 and 17 of textile component 12 according to an exemplary embodiment.
[0015] Figure 3 is an end view of textile component 12 illustrating filament entanglement between fabric structures 16 and 17 of textile component 12 according to an exemplary embodiment. DETAILED DESCRIPTION
[0016] In the following detailed description, reference is made to the accompanying drawings, which form a part of the detailed description and illustrate exemplary embodiments of the present invention. These embodiments will be described in sufficient detail to enable those of ordinary skill in the art to make and use them. It should also be understood that structural, logical or procedural changes may be made to the exemplary embodiments disclosed herein without departing from the spirit or scope of the present invention.
[0017] Figure 1 An exemplary exploded end view of one embodiment of a composite fire resistant sheet 11 is shown generally at 10. The composite sheet 11 includes a textile component 12 having a first surface 13 and a second surface 14 and a first polymer coating 15 disposed on the first surface 13 of the textile component 12. An optional second polymer coating 19 may be disposed on the second surface 14 of the textile component 12.
[0018] Textile parts
[0019] Textile component 12 includes two different textile structures.
[0020] The fabric structure 16 comprises at least one woven fabric of continuous filament yarns.
[0021] Fabric structure 17 is a nonwoven fabric of a blend of discontinuous fibers including oxidized polyacrylonitrile fibers and silica fibers. In some embodiments, the oxidized polyacrylonitrile fibers are present in an amount of about 30 to about 70 weight percent of the combined weight of the oxidized polyacrylonitrile fibers and the silica fibers, and in other embodiments, in an amount of about 40 to about 60 weight percent of the combined weight of the oxidized polyacrylonitrile fibers and the silica fibers. In some embodiments, the nonwoven fabric has an area weight of about 100 to about 170 gsm, in other embodiments about 100 to about 240 gsm, and in other embodiments about 100 to about 305 gsm. Preferably, fabric structure 17 includes only one nonwoven fabric, but more than one nonwoven fabric may be incorporated into fabric structure 17.
[0022] Fabric structure 16 of textile component 12 may be attached to fabric structure 17 by attachment means. Suitable attachment means for attaching fabric structures 16 and 17 together include, but are not limited to, bonding, sewing, or fiber entanglement.
[0023] Bonding may be achieved by placing an adhesive, preferably an adhesive film, between fabric structures 16 and 17 and curing the adhesive, or by impregnating one or both of fabric structures 16 and 17 with a matrix resin, placing fabric structure 16 in contact with fabric structure 17 and curing the matrix resin.
[0024] Figure 2 An example cross-sectional view of a stitching option is shown, wherein stitch 20 passes through two fabric structures 16 and 17 of textile component 12 .
[0025] Figure 3 An example of a cross-sectional view of a fiber entanglement option is shown. This is commonly referred to as needle punching or needling. In this process, fine needle barbs repeatedly penetrate the textile component 12, causing the filaments to reorient and extend in the z direction generally perpendicular to the xy plane of the textile component 12. This intermixing of the filaments 21 between the two fabric structures 16 and 17 improves the flame retardancy of the textile component.
[0026] In some embodiments, some combination of bonding, sewing, or fiber entanglement may be used as the attachment means.
[0027] When tested according to ASTM D1876-08 (2015) - Standard Test Method for Peel Resistance of Adhesives, the textile component 12 should preferably have a fabric-to-fabric bond strength of at least 11 kg / 10 cm when subjected to puncture, i.e., there is no delamination between the fabric structure 16 and the fabric structure 17 until a tensile strength of at least 11 kg / 10 cm is reached.
[0028] In some embodiments, one or more of the fabric structures 16 and 17 of the textile component 12 are impregnated with a matrix resin such that the resin is present in an amount of about 5 to about 45 weight percent of the combined weight of the resin and the fibers in each of the one or more impregnated fabric structures, in other embodiments, about 7 to about 40 weight percent of the combined weight of the resin and the fibers in each of the one or more impregnated fabric structures, in other embodiments, about 7 to about 20 weight percent of the combined weight of the resin and the fibers in each of the one or more impregnated fabric structures, and in other embodiments, about 15 to about 20 weight percent of the combined weight of the resin and the fibers in each of the one or more impregnated fabric structures. The matrix resin can be a phenolic resin, a flame retardant epoxy resin, or a flame retardant polyurethane. Bio-based resins such as bio-based perfluoroalkoxy copolymers, bio-based epoxy glass polymer materials, bio-based polyetherimides, lignin bio-based phenolic resins, bio-based polycarbonates, soy-based unsaturated polyesters, bio-based benzoxazines, bio-based epoxy resins, and green polyethylene can also be used. The resin is cured according to the recommended curing cycle from the supplier. A continuous belt press is an example of a piece of equipment where the curing process may be affected.
[0029] In a preferred embodiment, both fabrics 16 and 17 are impregnated with a matrix resin. In yet another embodiment, both fabric structures 16 and 17 are attached to each other by attachment means and are impregnated with a matrix resin.
[0030] Embodiments in which at least one textile structure 16 or 17 of the textile component 12 is impregnated with resin provide a composite sheet 11 that is rigid and has limited roll-up capability. Embodiments in which the textile component 12 is not impregnated with resin provide a semi-rigid (i.e., flexible and rollable) composite sheet 11.
[0031] Woven fabrics
[0032] Suitable weave patterns for the one or more woven fabrics of the fabric structure 16 include plain weave, satin weave, basket weave, leno weave, or twill weave. A suitable fabric for the one or more woven fabrics of the fabric structure 16 is a 1500 denier 29 para-aramid yarn, clean, 230 gsm, 17×17 (pick count), plain weave fabric. Alternatively, the one or more woven fabrics of fabric structure 16 can be a plain weave fabric containing 555 dtex (500 denier) KM2+ para-aramid yarn in both the warp and weft directions, in an amount of 11 ends / cm (28 ends / inch). Where there is more than one woven fabric in fabric structure 16, the woven fabrics can be the same or different in yarn composition and / or weave pattern. In some embodiments, the one or more woven fabrics of fabric structure 16 have an area weight of about 70 to about 508 gsm (2.1 to 15 ounces / square yard), in other embodiments, about 101 to about 373 gsm (3 to 11 ounces / square yard), and in other embodiments, about 101 to about 170 gsm (3 to 5 ounces / square yard).
[0033] In some embodiments, one or more woven fabrics of fabric structure 16 are washed or heat cleaned after weaving. Such processes are well known in the textile industry to remove contaminants such as oils from the weaving process.
[0034] One or more woven fabrics of fabric structure 16 are made of multifilament yarn with multiple filaments. Yarn can be wound and / or twisted. For the purpose of this paper, term " long filament " is defined as a relatively flexible, macroscopically uniform body with high aspect ratio across its cross section perpendicular to its length. This filament cross section can be any shape but is typically circular or bean-shaped. In this article, term " fiber " can be used interchangeably with term " long filament ", and when relating to warp and weft density, term " single line (end) " can be used interchangeably with term " yarn ".
[0035] The filaments can have any length. Preferably, the filaments are continuous. The multifilament yarn spun to the bobbin in the package contains a plurality of continuous filaments. The multifilament yarn can be cut into staple fibers and made into a spun staple yarn suitable for use in one or more woven fabrics of the fabric structure 16. The staple fibers can have a length of about 1.5 to about 5 inches (about 3.8 cm to about 12.7 cm). The staple fibers can be straight (that is, non-curled) or curly with a zigzag curl along its length, wherein the curl (or repeated bending) frequency is about 3.5 to about 18 curls / inch (about 1.4 to about 7.1 curls / cm).
[0036] In some embodiments, the yarns of the one or more woven fabrics of fabric structure 16 have a yarn tenacity of at least about 11 g / dtex and a modulus of at least about 100 g / dtex. In some embodiments, the yarns of the one or more woven fabrics of fabric structure 16 have a linear density of about 333 to about 2222 dtex (300 to 2000 denier), in other embodiments about 555 to about 1111 dtex (500 to 1000 denier), in other embodiments about 555 dtex, and in other embodiments about 1111 dtex.
[0037] The fibers of the yarns of the fabric structure 16 can be polymeric, inorganic or natural and can be made of any suitable material known in the art. In some embodiments, the fibers of the yarns can be aromatic polyamides, aromatic copolyamides, aliphatic polyamides, polyolefins, polyazoles, glass, carbon, multicomponent fibers, and combinations thereof.
[0038] When the polymer is a polyamide, aramid is preferred. As used herein, "aramid" means a polyamide polymer in which at least 85% of the amide (-CONH-) linkages are directly attached to two aromatic rings. Para-aramid polymers are aramid polymers in which the amide linkages are in a para position relative to each other. A preferred para-aramid polymer is poly(p-phenylene terephthalamide) or PPD-T. Additives can be used with aramids, and in fact it has been found that other polymeric materials up to 10 weight percent can be blended with the aramid, or copolymers can be used, which have up to 10% of other diamines replacing the diamines of the aramid or up to 10% of other diacid chlorides replacing the diacid chlorides of the aramid. Suitable aramid fibers are described in Man-Made Fibres-Science and Technology, Volume 2, in the section entitled Fibre-Forming Aromatic Polyamides, page 297, W. Black et al., Interscience Publishers, 1968. Aramid fibers and their production are also disclosed in U.S. Pat. Nos. 3,767,756; 4,172,938; 3,869,429; 3,869,430; 3,819,587; 3,673,143; 3,354,127; and 3,094,511.
[0039] Other useful para-aramids include aramid copolymers derived from combinations and / or substitutions of other aromatic diamines and other aromatic diacid chlorides, such as, for example, 2,6-naphthaloyl chloride or chloroterephthaloyl chloride or dichloroterephthaloyl chloride or 3,4'-diaminodiphenyl ether. Another preferred para-aramid includes aromatic polyamide copolymers derived from 5(6)-amino-2-(p-aminophenyl)benzimidazole (DAPBI), p-phenylenediamine (PPD) and terephthaloyl dichloride (TC1 or T, also commonly referred to as terephthaloyl chloride); for example, as in U.S. Patent Publication No. 2014 / 0357834, Russian Patent Application No. 2,045,586, and other such fibers provided in, for example, Sugak et al., Fibre Chemistry, Vol. 31, No. 1, 1999; U.S. Patent No. 4,018,735; and WO 2008 / 061668 and US 2014 / 357834-A1.
[0040] Examples of commercially available para-aramid fibers include aramid fibers from DuPont of Wilmington, Delaware. and Teijin Aramid from Arnhem, the Netherlands Examples of aramid copolymer fibers include aramid copolymer fibers from Kamenskvolokno Company, Kamensk-Shakhtinskii, Russia. and
[0041] Glass fibers can include "E" glass and "S" glass. E-glass is a commercially available low-alkali glass. A typical composition consists of 54 wt% SiO2, 14 wt% Al2O3, 22 wt% CaO / MgO, 10 wt% B2O3, and less than 2 wt% Na2O / K2O. Some other materials may also be present at impurity levels. S-glass is a commercially available magnesium oxide-aluminum oxide-silicate glass. This composition is harder and stronger than E-glass and is commonly used in polymer matrix composites. Exemplary woven fabrics of fabric structure 16 include, but are not limited to, heat-cleaned weave pattern 7781 with E-glass yarns and weave pattern 6781 with S-glass yarns.
[0042] Suitable carbon fibers are standard or intermediate modulus fibers such as those available from Toray Industries under the trade name Torayca or from Hexcel Corporation as HexTow. Typically such fibers have 3,000 or 6,000 or 12,000 or 24,000 filaments per bundle.
[0043] In some embodiments, the fabric structure 16 may be optionally treated with a flame retardant composition. Suitable flame retardant compositions include, but are not limited to, antimony trioxide, halogenated flame retardants (including tetrabromobisphenol A, polybrominated biphenyls, pentabromodiphenyl ether (oxide), octabromodiphenyl ether (oxide), decabromodiphenyl ether (oxide), and hexabromocyclododecane). Phosphorus-containing flame retardants are also widely used.
[0044] Polymer coating
[0045] The polymer of the first polymer coating 15 or the second polymer coating 19 may be a thermoplastic polymer or a thermosetting polymer or a silicone rubber.
[0046] Suitable polymers include polyurethane, polyethylene, polypropylene, polyethylene naphthalate, polyacrylonitrile, fluoropolymers, polyimide, polyketone, polyimide Polysulfones, polyarylene sulfides, liquid crystal polymers, polycarbonates, and ionomers such as ethylene methacrylic acid copolymers (E / MAA).
[0047] Exemplary fluoropolymers include polyvinyl fluoride Ethylene chlorotrifluoroethylene copolymer and polytetrafluoroethylene Exemplary polyketones include polyetheretherketone (PEEK) and polyetherketoneketone (PEKK).
[0048] In one embodiment, the first polymer coating 15 is a polyurethane. In another embodiment, the second polymer coating 19 is an ionomer resin (such as ethylene methacrylic acid copolymer). In yet another embodiment, the first polymer coating 15 is opaque and opaque to UV rays. By opaque and opaque to UV rays, we mean that at least 95% of the UV rays, more preferably at least 98% and most preferably 100% of the UV rays are blocked, especially those at the upper end of the UV spectrum.
[0049] In some embodiments, the first polymer coating 15 and / or the second polymer coating 19 has an area weight of about 17 to about 170 gsm (0.5 to 5 ounces per square yard), in other embodiments, about 34 to about 136 gsm (1 to 4 ounces per square yard), and in other embodiments, about 67 to about 102 gsm (2 to 3 ounces per square yard).
[0050] Preferably, the first and second polymer coatings 15 and 19 can be polyurethane, silicone rubber, polyvinyl chloride or a blend thereof, respectively. In some embodiments, the second polymer coating 19 can be an ionomer resin based on ethylene acid copolymer (e.g. ).
[0051] First polymer coating 15 contacts first surface 13 of textile component 12 and provides chemical and environmental (ie, weather and UV) resistance to both physical and chemical attack and liquid penetration.
[0052] By chemical and environmental / weather resistance is meant the ability of the polymer coating to withstand the effects of wind, rain, contaminants (such as acidic and / or oily residues) found in typical industrial areas, and sunlight exposure without excessive degradation. Preferably, the first polymer coating 15 has enhanced resistance to damage caused by chemical reactivity or solvent action from hydrocarbons, chemicals, ozone, bacteria, fungi and moisture, as well as skin care oils typically associated with the operation and maintenance of commercial aircraft.
[0053] UV resistant means that when exposed to ultraviolet radiation, the first polymer coating 15 maintains its appearance and physical integrity without excessively reducing its flexibility or mechanical properties (i.e., brittleness). Preferably, the polymer layer blocks at least 95% of UV rays, more preferably at least 98% and most preferably 100% of UV rays. The UV opacity of the polymer coating 15 can be further mitigated by including additives in the polymer material. Examples of such additives include fillers, pigments, stabilizers, and lubricants. The outer surface of the first polymer coating 15 that is not in contact with the fabric structure 16 can be optionally coated or treated with a UV blocking material.
[0054] Ultraviolet (UV) is an invisible band of radiation at the upper end of the visible spectrum. At wavelengths ranging from 10 to 400 nm, ultraviolet (UV) begins at the end of visible light and ends at the beginning of X-rays. Since the primary exposure of the composite sheet 11 to UV light is the sun, the most critical UV resistance is to the lower frequency, longer wavelength rays.
[0055] Preferably, the first polymer coating 15 has a soft, non-plastic feel, which is ideal for products that come in contact with human skin, and maintains its toughness and flexibility over a wide temperature range, even at temperatures as low as -50°C (-60°F), over the useful life of the product.
[0056] In some embodiments, the outer surface of the first polymer coating 15 (i.e., the surface not in contact with the fabric structure 16) has a release value of no more than 263 N / m (1.5 lb. / in), more preferably no more than 438 N / m (2.5 lb. / in), when measured according to ASTM D2724-07 (2011) e1 Standard Test Methods for Bonded, Fused, and Laminated Apparel Fabrics. This facilitates cleaning, label removal, etc.
[0057] In some embodiments, the fabric structure 16 can be bonded to the first polymer coating 15 by means (such as adhesives, thermal bonding) or by fasteners. Such adhesives can be thermoplastic or thermosetting resins. Thermosetting resins include, but are not limited to, epoxy resins, epoxy novolacs, phenolic resins, polyurethanes, and polyimides. Thermoplastic resins include, but are not limited to, polyesters, polyetherketones, polyetheretherketones, polyetherketoneketones, polyethersulfones, and polyolefins. Thermoplastic resins are preferred.
[0058] Preferably, the adhesive may optionally contain up to about 40 weight percent of a flame retardant component. Suitable flame retardant components include, but are not limited to, antimony trioxide, halogenated flame retardants (including tetrabromobisphenol A, polybrominated biphenyls, pentabromodiphenyl ether (oxide), octabromodiphenyl ether (oxide), decabromodiphenyl ether (oxide), and hexabromocyclododecane). Phosphorus-containing flame retardants are also widely used.
[0059] Preferably, the adhesive blocks at least about 95% of UV rays, more preferably at least about 98% and most preferably about 100% of UV rays.The adhesive may further contain fillers, pigments, stabilizers, and other performance enhancing additives.
[0060] Preferably, the adhesive bond between the first polymer coating 15 and the fabric structure 16 is at least about 263 N / m (1.5 lb. / in). In some embodiments, the adhesive bond between the first polymer coating 15 and the fabric structure 16 is at least about 438 N / m (2.5 lb. / in), and in other embodiments is about 876 N / m (5 lb. / in).
[0061] The second polymer coating 19, which is the innermost layer of the composite sheet 11, contacts the second surface 14 of the textile component 12. The second polymer coating 19 may also be colored and contain an ultraviolet (UV) blocker. Acceptable UV resistance is the ability to withstand exposure to strong direct sunlight for 10 years without compromising the basic mechanical and visual properties of the sheet. A suitable standard is ASTM G154-16 (UVA-340 lamp, 16 hours of UV at 60°C ± 2°C over a period of 240 hours, and 8 hours of condensation at 50°C ± 2°C.
[0062] In some embodiments, the fabric structure 17 can be bonded to the second polymer coating 19 by suitable bonding means (eg, adhesive, thermal bonding) or by fasteners. An adhesive similar to that described above for bonding the fabric structure 16 to the first polymer coating 15 can be used here.
[0063] Typical coatings for the first or second polymer coatings 15 and 19 have a thickness of about 75 microns and an area weight of about 90 gsm. The coatings should have a vertical flame flammability rating in accordance with UL 94V-0 and be able to withstand exposure from -40 to +60 degrees Celsius without compromising basic mechanical and visual properties (such as flexibility, color, transparency, etc.).
[0064] Practicality
[0065] The composite sheet 11 described herein has useful fire resistant properties and is suitable as a curtain wall material for cargo containers, particularly containers used in aircraft. Aircraft cargo containers are often referred to as unitary load devices (ULDs). In a preferred embodiment, when assembled into a container frame, the composite sheet 11 is positioned so that the structure 17 of the textile component 12 is positioned to face the fire threat from the cargo. The fire threat direction is determined by Figure 1 The composite sheet 11 complies with the test method described below.
[0066] The term "innermost" as used in the present disclosure refers to the portion of the composite sheet facing the cargo when the composite sheet 11 is assembled into a cargo container. The term "outermost" as used in the present disclosure refers to the portion of the composite sheet farthest from the cargo when the composite sheet 11 is assembled into a cargo container.
[0067] The composite sheet 11 will also be able to provide useful fire resistance properties when exposed to a fire on the exterior of a cargo container where the first structure 16 will be facing the flames.
[0068] Test Method
[0069] Flame penetration is measured in accordance with 14 CFR 25.855 Appendix F Part III - Test Method to Determine Flame Penetration Resistance of Cargo Compartment Liner (ceiling position). This is referred to as "Test Method 1" in the examples.
[0070] The composite sheet was subjected to a flame test that replicated the temperature and air mass flux test conditions of Test Method FAA FAR 25.856(b) Appendix F, Part VII. The slightly lower heat flux was compensated by a higher air mass flux to replicate the required thermomechanical stress levels imposed on the flame retardant composite sheet during the burn-through test. This is referred to as "Test Method 2" in the Examples.
[0071] The wash-dry cycle consisted of a 4 lb. load with each warm water wash cycle having a duration of 40 minutes. The detergent was 66 g of 1993 AATCC Standard Reference Detergent. Each drying cycle lasted 40 minutes and the drying medium was forced cold air.
[0072] Examples
[0073] The following examples are given to illustrate exemplary embodiments of the present invention and should not be construed as limiting the present invention in any way. Unless otherwise indicated, all parts and percentages are by weight. Examples prepared according to one or more processes described herein are indicated by numerical values. Control examples or comparative examples are indicated by letters.
[0074] Example 1
[0075] Textile component 12 such as Figure 1 The textile structure 16 of the textile component 12 is a 230 gsm plain weave woven from 1500 denier yarns. The fabric structure 17 of the textile component 12 is a nonwoven fabric from Tex Tech Industries of North Monmouth, ME. The nonwoven fabric has a nominal weight of 239 gsm and contains 50 weight percent of pre-oxidized polyacrylonitrile fiber type ZOLTEK TM OX and 50 weight percent Beloctex TM Silica Fiber.
[0076] The two textile structures 16 and 17 are mechanically attached to each other by needling. In this example there are no first or second polymer coatings 15 and 19.
[0077] Two samples of textile component 12 were subjected to a wash-dry cycle, and two samples were not subjected to a wash-dry cycle to serve as controls.
[0078] Two additional samples of textile component 12 were used 445D05 The phenolic resin is impregnated such that the resin content is nominally 28.0 weight percent of the combined weight of the polyacrylonitrile fibers, silica fibers, and resin. The resin is then cured to obtain a rigid textile component 12.
[0079] All six sample specimens of Example 1 were subjected to and passed Test Method 2. In this test, the fabric structure 17 faced the flame.
[0080] It was also observed that the test specimens subjected to the wash-dry cycle had less smoke and off-gassing during the flame test than the unwashed test specimens.
[0081] A further observation between the six samples of Example 1 was that after flame exposure, the resin impregnated samples had significantly better residual cohesive integrity than the unimpregnated samples, with the washed samples showing lower residual cohesive integrity after flame exposure than the unwashed samples.
[0082] Example 2
[0083] This example was prepared in the same manner as in Example 1, except that the fabric structure 17 had an area weight of 307 gsm. The two fabrics 16 and 17 were mechanically attached to each other by needling.
[0084] Test specimens were prepared as in Example 1. All six specimens were subjected to and passed Test Method 2. In this test, the fabric structure 17 faced the flame.
[0085] There were no significant performance differences between the corresponding washed, unwashed and resin impregnated specimens of Examples 1 and 2, nor were there any noticeable differences in appearance or levels of physical degradation between corresponding specimens of these two samples during and after flame exposure.
[0086] Example 3
[0087] The textile component 12 is the same as in Example 1. The two fabrics 16 and 17 are mechanically attached to each other by needling. The textile component 12 is not impregnated with resin and thus a flexible textile component 12 is obtained.
[0088] An opaque 0.075 mm (3 mil) cast polyurethane film was thermally bonded to both first surface 13 and second surface 14 of an unwashed sample of textile component 12, thereby providing first polymer coating 15 and second polymer coating 19, respectively.
[0089] This example was subjected to and passed Test Method 2. In this test, the second polymer coating 19 was exposed to a flame with the fabric structure 17 immediately adjacent to the second polymer coating 19.
[0090] Example 4
[0091] The textile component 12 is the same as in Example 1. The two fabrics 16 and 17 are mechanically attached to each other by needling. 445D05 The phenolic resin was impregnated such that the resin content was nominally 28.0 weight percent of the combined weight of the polyacrylonitrile fibers, silica fibers, and resin. The resin was then cured to obtain a rigid textile component.
[0092] An opaque 0.075 mm (3 mil) cast polyurethane film was thermally bonded to both first surface 13 and second surface 14 of textile component 12, thereby providing first polymer coating 15 and second polymer coating 19, respectively.
[0093] This example was subjected to and passed Test Method 2. In this test, the second polymer coating 19 was exposed to a flame with the fabric structure 17 immediately adjacent to the second polymer coating 19.
[0094] Comparative Example A
[0095] The textile component 12 of this example includes a 1500 denier K29 yarn woven plain weave para-aramid fabric having 26 ends / inch in both the warp and weft and 190 gsm plain weave E-glass fabric (ECG). Neither fabric was mechanically entangled by needle punching, nor was the textile component impregnated with resin. No first or second polymer coating 15 or 19 was present in this example. This example failed Test Method 1, thus demonstrating the benefit provided by the second structure 17 as previously described in providing enhanced flame retardant properties.
[0096] Comparative Example B
[0097] This example was prepared in the same manner as in Example 1, except that the second structure 17 was omitted. In this example, there was no first or second polymer coating 15 or 19. The unwashed structure failed both Test Methods 1 and 2, thus demonstrating the benefit provided by the second structure 17 in providing enhanced flame retardant properties.
[0098] Comparative Example C
[0099] The textile component 12 of this example is as follows Figure 1 The fabric structure 16 is made of 1500 denier A plain weave para-aramid fabric woven with K29 yarn. This aramid fabric has 26 ends / inch in both the warp and weft. The fabric structure 17 of the textile component 12 is a nonwoven fabric from Texas Tech Industries. This nonwoven fabric has a nominal weight of 170 gsm and contains 50 weight percent pre-oxidized polyacrylonitrile fiber type ZOLTEK TM OX and 50 weight percent Beloctex TM Silica fiber. The textile component 12 is needle-punched but not impregnated with resin. There is no first or second polymer coating 15 or 19 in this example. In addition, the sample was not washed. Although the performance was good in the first two minutes of the flame test (where the textile structure 17 faced the flame), the performance in the remaining three minutes was lower than expected, and therefore the example was considered to have failed Test Method 2 and Test Method 1. This is attributed to the lower area weight of the second structure 17. Although it failed Test Methods 1 and 2, the composite sheet of this example may be suitable for less demanding fire resistant applications.
Claims
1. A composite sheet comprising a textile component having a first surface and a second surface and a first polymer coating on the first surface of the textile component, wherein the textile component further comprises a first fabric structure of at least one woven fabric of continuous filament yarn, the woven fabric having an area weight of about 70 to about 508 gsm, and A second fabric structure of a nonwoven fabric comprising a blend of discontinuous fibers of oxidized polyacrylonitrile fibers and silica fibers, wherein the oxidized polyacrylonitrile fibers are present in an amount of about 30 to about 70 weight percent of the combined weight of the oxidized polyacrylonitrile fibers and silica fibers.
2. The composite sheet of claim 1, further comprising a second polymer coating on the second surface of the textile component.
3. The composite sheet according to claim 1, wherein: The filaments of the at least one woven fabric of the first fabric structure are aramid, aramid copolyamide, glass, carbon, or aliphatic polyamide.
4. The composite sheet according to claim 1, wherein: At least one of the first fabric structure and the second fabric structure is impregnated with a matrix resin.
5. The composite sheet according to claim 1, wherein: The first polymer coating on the first surface of the textile component is polyurethane, silicone rubber, polyvinyl chloride, or a blend thereof.
6. The composite sheet according to claim 1, wherein: The first structure and the second structure are attached to each other by attachment means.
7. The composite sheet according to claim 1, wherein: The at least one woven fabric of the first fabric structure has an area weight of at least 203 gsm.
8. The composite sheet according to claim 2, wherein: The second polymer coating on the second surface of the textile component is polyurethane, silicone rubber, polyvinyl chloride, ethylene acid copolymer, or a blend thereof.
9. The composite sheet according to claim 3, wherein: The aramid filaments of the at least one woven fabric of the first fabric structure are para-aramid.
10. The composite sheet according to claim 4, wherein: The matrix resin is a phenolic resin, a flame retardant epoxy resin, a flame retardant polyurethane, or a bio-based resin.
11. The composite sheet according to claim 4, wherein: The resin is present in an amount of about 5 to about 45 weight percent of the combined weight of the resin and fibers in the at least one of the first fabric structure and the second fabric structure.
12. The composite sheet according to claim 6, wherein: The attachment means are adhesion, sewing, or fiber entanglement.
13. The composite sheet according to claim 7, wherein: The nonwoven fabric of the second fabric structure has an area weight of at least 237 gsm.
14. A cargo container comprising the composite sheet according to claim 1.
Citation Information
Patent Citations
Composite sheet and cargo container comprising same
US10300677B2
Composite sheet and cargo container comprising same
US10457013B2
Aramid copolymer yarn having low residual sulfur
US20140357834A1
Cutting machine
US2045586A
Wholly aromatic polyamides
US3094511A